Desain Sistem Daily Pre Trip Inspection Di SBU Pemeliharaan Dan Perbaikan Perum PPD Berbasis Android - Kusuma, Raffi Wahyu; Laksana, Singgih; Masruchan, Muhammad (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2018)
Daily pre trip inspection is a checking activity conducted by Djakarta Passenger Public Company (Perum PPD)before the vehicle operates on the road. In fact, there is still a lot of damage causing the decline in the numberof buses that operate. In addition, the inspection is done manually using the paper media checklist formresulting in data loss checking, writing is not clear, the data is not recorded properly to the detriment of thecompany. This research uses qualitative analysis with descriptive method resulted in standard operatingprocedure design (SOP) daily pre trip based inspection android. Combining existing check sheets is enhancedby Government Regulation No. 55/2012 on technical requirements and road worth of vehicles, Decree of theDirector General of Land Transportation No. 523 of 2015 on guidelines for the implementation of traffic safetyinspection and public transport of roads, and adjusted to the standard of checks HINO, generate a new checksheet. With the new SOP utilizing android applications, is expected to reduce the company's losses, bus damageand accidents while operating.